Measuring Ethical Ideology in Business Ethics: A Critical Analysis of the Ethics Position Questionnaire - Davis, Mark A. (Journal of business ethics, 2001)
Individual differences in ethical ideology are believed to play a key role in ethical decision making. Forsyth’s (1980) Ethics Position Questionnaire (EPQ) is designed to measure ethical ideology along two dimensions, relativism and idealism. This study extends the work of Forsyth by examining the construct validity of the EPQ. Confirmatory factor analyses conducted with independent samples indicated three factors – idealism, relativism, and veracity – account for the relationships among EPQ items. In order to provide further evidence of the instrument’s nomological and convergent validity, correlations among the EPQ subscales, dogmatism, empathy, and individual differences in the use of moral rationales were examined. The relationship between EPQ measures of idealism and moral judgments demonstrated modest predictive validity, but the appreciably weaker influence of relativism and the emergence of a veracity factor raise questions about the utility of the EPQ typology.